2013
DOI: 10.1080/08905436.2012.724037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fermentation of Pomegranate Juice byLactobacillus plantarumandLactobacillus acidophiluson the Antioxidant Activity and Metabolism of Sugars, Organic Acids and Phenolic Compounds

Abstract: The effect of lactic acid bacterial fermentation on sugars, organic acids, bio-transformation of phenolic compounds (anthocyanins and ellagic acid), and antioxidant activity was investigated in pomegranate juice. L. plantarum and L. acidophilus were used as probiotic starter organisms. Both bacteria were able to grow in the juice and their viable cells reached to 3.9×10 8 CFU/mL after 72 h of fermentation. Fructose and glucose of the juice were significantly consumed by both probiotic starter cultures, and L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
102
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(127 citation statements)
references
References 25 publications
18
102
1
6
Order By: Relevance
“…They are very sensitive to the action of β-glucosidase, which causes disruption of bonds with sugar radicals, leading to the formation of anthocyanidins, which exhibits a greater capacity to inhibit free radicals. This enzyme is produced by lactic acid bacteria Lactobacillus and yeasts from the genus Saccharomyces [35,36].…”
Section: Stability Of Anthocyaninsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are very sensitive to the action of β-glucosidase, which causes disruption of bonds with sugar radicals, leading to the formation of anthocyanidins, which exhibits a greater capacity to inhibit free radicals. This enzyme is produced by lactic acid bacteria Lactobacillus and yeasts from the genus Saccharomyces [35,36].…”
Section: Stability Of Anthocyaninsmentioning
confidence: 99%
“…Operations preceding fermentation include enzymolysis, clarification, filtration and sterilization. Due to high contents of enzymes-polyphenol oxidase and β-glucosidase, potentially influencing the composition of phenolics, enzymolysis is run in order to inhibit their activity [16,35,36]. Clarification and microfiltration aim at the elimination of sediment and clouding, which deteriorate sensory attributes of juice.…”
Section: Analysis Of the Effect Of Fermentation On Bioactive Componenmentioning
confidence: 99%
“…Moreover, due to high carbohydrates content and acidity, it can be considered as a favourable substrate for fermentation process to produce organic acids, especially glucuronic acid (Kazakos et al, 2016). Furthermore, Mousavi et al (2013Mousavi et al ( & 2011 emphasized the fermentation suitability of pomegranate juice, as a functional beverage.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on pomegranate juice fermentation, as a single or mixed substrate, using kefir grains (Kazakos et al, 2016), Saccharomyces cerevisiae yeast strains (Berenguer et al, 2016), and lactic acid bacteria (Lactobacillus acidophilus and plantarum) (Mousavi et al, 2013;Filannino et al, 2013) have been reported. However, so far, no analyses considered using kombucha symbiosis layer to ferment pomegranate juice to evaluate the functional properties of produced fermented beverages (in terms of glucuronic acid content) has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar da maioria dos autores relatarem a preferência pelo consumo de glicose em relação ao consumo de frutose (SILVA et al, 2010;PAUCEAN et al, 2013;MOUSAVI et al, 2013), houve diferença significativa (p < 0,05) entre as concentrações de frutose nas primeiras 24 h, mas não houve diferenças significativas (p > 0,05) nas concentrações de glicose ao longo do tempo de fermentação, revelando o favorecimento do consumo de frutose. Com base nos resultados, pode haver uma preferência do L. plantarum CCT 0580 por AR ao invés da sacarose.…”
Section: Resultsunclassified